PROFIL BERPIKIR KREATIF SISWA LAKI-LAKI DAN PEREMPUAN KELAS VIII SMP NURIS JEMBER DALAM MENYELESAIKAN SOAL CERITA POKOK BAHASAN SEGIEMPAT - Irvani, Fajrin Abidiyah; Suharto, Suharto; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2016)
Abstract. This research aims to describe the creative thingking profile boys and girls in eighth grade of SMP Nuris Jember in solving story question about rectangle. This research’s type is descriptive research with qualitative approach. Data collection methods which are used in this research are test and interview. Subject for this research are three boys student and three girls student of class VIII C SMP Nuris Jember. The characteristics of creative thingking are fluency, flexibility, and novelty. In real problem there are four steps to solve the question is understand the problem, make a plan to solve the problem, implement the resolution of problem, and checking back the answer . The results of this research showed that the boys student can explain the problem and the resolution verbally but less able to explain by writing. While the girls student can explain the problem and the resolution either verbally or in writing. Key Words: Critical Creative Thingking, Story Question, Rectangle, The Boys and Girls Student